CEST MRI of 3‐O‐methyl‐D‐glucose on different breast cancer models. Issue 2 (12th May 2017) - Rivlin, Michal; Navon, Gil
Abstract : Purpose: To test the ability of chemical exchange saturation transfer (CEST) MRI of 3‐O‐methyl‐D‐glucose (3OMG) to detect tumors in several breast cancer models of murine and human origin, for different routes of administration of the agent and to compare the method with glucoCEST and with 18 FDG‐PET on the same animals. Methods: In vivo CEST MRI experiments were performed with a 7T Biospec animal MRI scanner on implanted orthotopic mammary tumors of mice before and after administration of 3OMG. Results: A marked 3OMG‐CEST MRI contrast that was correlated with the administrated dose was obtained in different breast cancer models and by intravenous, intraperitoneal, and per os methods of administration. The most aggressive breast cancer model yielded the highest CEST contrast. 3OMG‐CEST contrast reached its maximum at 20 min after administration and lasted for more than an hour, while that of glucose was lower and diminished after 20 min. 3OMG‐CEST showed comparable results to that of FDG PET. Conclusion: The sensitivity of the 3OMG‐CEST MRI method indicates its potential for the detection of tumors in the clinic. Magn Reson Med 79:1061–1069, 2018. © 2017 International Society for Magnetic Resonance in Medicine.